Strengthening students' religious well-being through spiritual reflection-based islamic religious education learning - Dwiki Al Akhyar (Asian Journal of Islamic Studies and Society, 2025)
This study investigated the effectiveness of spiritual reflection-based Islamic Religious Education (IRE) learning in strengthening students' religious well-being. Religious well-being, conceptualized through Ellison's (1983) multidimensional framework, encompasses an individual's perceived closeness to God, existential meaning, and spiritual connectedness, all of which profoundly influence psychological, social, and educational outcomes. Despite growing international scholarship on reflective pedagogy and spiritual education, empirical research integrating muhasabah-based reflective practices within quasi-experimental Islamic educational settings remains scarce in the Indonesian secondary education context. This study addresses this gap by employing a quantitative quasi-experimental pretest-posttest control group design involving 68 senior high school students (n = 34 experimental; n = 34 control) from a vocational high school in South Sumatra, Indonesia. Participants were aged 15–17 years (M = 16.2), with 52.9% female and 47.1% male. Data were collected using a validated Religious Well-Being Scale (30 items; α = .87), structured observations, in-depth interviews, and learning documentation across eight instructional sessions. Results demonstrated a statistically significant improvement in religious well-being among the experimental group (M pretest = 68.42; M posttest = 86.75; N-Gain = 0.71, high category) compared to the control group (M pretest = 67.88; M posttest = 74.36; N-Gain = 0.29, low-to-moderate category). Independent samples t-test confirmed a significant between-group difference (t(66) = 7.84, p < .001, d = 1.90). Qualitative findings identified four dominant themes: spiritual awareness, gratitude enhancement, emotional regulation, and religious commitment. These findings provide empirical support for integrating spiritually transformative pedagogical approaches within Islamic Religious Education curricula, contributing to both educational theory and practice.